What Learning Is Reported in Social Science Classroom Interventions? a Scoping Review of the Literature - Valencia-Castaneda, L; Miranda-Arredondo, P (Elsevier Ltd, 2022)
This review analyzes the learning reported in social science classroom interventions in primary and secondary school education over the last ten years. Thirty-three studies found in a scoping review were analyzed. They were analyzed using the two main perspectives of social sciences teaching and learning: each discipline individually (History, Geography) and an interdisciplinary approach (Social Studies). Results show most interventions followed the disciplinary perspective, and amongst them, they mainly focused on the History subject. Most interventions explained the development of disciplinary skills, such as contextualization and historical thinking, giving less emphasis to the content and attitudes. Few studies are positioned in an interdisciplinary perspective, evidencing a significant research gap in social sciences learning. Literature indicates that if Social Sciences are taught and learned in an interdisciplinary manner, they have the potential to develop citizenship education. Therefore, teachers should move towards the interdisciplinary perspective to promote social thinking in their students. © 2022